Remittances as Social Practices and Agents of Change The Future of Transnational Society - Meyer, Silke; Ströhle, Claudius (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book explores the transformative effects of remittances. Remittances are conceptualized as flows of money, objects, ideas, traditions, and symbolic capital, mapping out a cross-border space in which people live, work, and communicate with multiple belongings. By doing so, they effect social change both in places of origin and destination. However, their power to improve individual living conditions and community infrastructure mainly results from global inequality. Hence, we challenge the remittance mantra and go beyond the migration-development-nexus by revealing dependencies and frictions in remittance relations. Remittances are thus scrutinized in their effects on both social cohesion and social rupture. By highlighting the transformative effects of remittance in the context of conflict, climate change, and the postcolonial, we shed light on the future of transnational society. Presenting empirical case studies from Ghana, Burkina Faso, Sri Lanka,New Zealand, Turkey, Lebanon, USA, Japan, and various European countries, as well as historical North America and the Habsburg Empire, we explore remittance relations from a range of disciplines including anthropology, sociology, history, design, architecture, governance, and peace studies. Silke Meyer is Professor of European Ethnology at the University of Innsbruck, Austria, where she also heads the research area "Cultural Encounters - Cultural Conflicts." She has published widely on economic anthropology, money practices and debts, as well as remittances and migration, and previously headed the research project "Follow the Money: Remittances as Social Practices" (funded by the Austrian Science Fund, 2016-2020). Claudius Ströhle is a Research Fellow in the Doctoral Program "Dynamics of Inequality and Difference in the Age of Globalization" at the University of Innsbruck, Austria. In the research project "Follow the Money: Remittances as Social Practices," he explored the transformative effects of remittances in Austria and Turkey. As part of his fellowship at the International Research Center for Cultural Studies (IFK) in Vienna, Austria, Claudius is currently a Visiting Scholar at the Institute of European Studies (IES) at UC Berkeley, USA.